A general size- and trait-based model of plankton communities. (November 2020) - Serra-Pompei, Camila; Soudijn, Floor; Visser, André W.; Kiørboe, Thomas; Andersen, Ken H.
Abstract: Multicellular zooplankton, such as copepods, are the main link between primary producers and fish. Most models of plankton communities, such as NPZ-type models, ignore the life-cycle (ontogeny) of multicellular zooplankton. Ontogeny has profound implications on population dynamics and community structure. Our aim is to provide a generic food-web framework of planktonic communities that accounts for zooplankton ontogeny. We propose a model framework along the Nutrient–Unicellular–Multicellular axis – a "NUM" framework – as an alternative to the NPZ modelling paradigm. NUM is a mechanistic size- and trait-based model based on traits and trade-offs at the individual level. Here the multicellular component describes the population dynamics of key copepod groups, characterized by their adult size and feeding mode. The unicellular compartment accounts for auto- mixo- and heterotrophic protists. We also consider nitrogen dynamics and carbon export from copepod fecal pellets. All parameters have been fitted to cross-species data. By approximate analytical solutions and dynamic simulations, in both constant and seasonal environments, we investigate the patterns of body sizes and traits that emerge within the community. We show that copepods of several adult sizes and feeding modes commonly coexist, and that competition and predation by large copepods on small/juvenile copepods is an important factor in shaping the community. We also show competition between heterotrophic protists and small copepods through intraguild predation. Finally, we discuss how copepods can attenuate the fecal pellet export. This conceptually simple, yet realistic framework opens the possibility to improve end-to-end size-structured models of marine systems and investigate biogeochemical processes. Highlights: We developed a generic food-web framework of planktonic communities with ontogeny. The model is mechanistic and based on traits and trade-offs at the individual level. We investigate the emergent patterns of plankton body sizes and traits.